2022
DOI: 10.1155/2022/2930960
|View full text |Cite|
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Hepatocyte-Derived lncRNA MALAT1 Aggravates Pancreatic Cell Inflammation via the Inhibition of Autophagy by Upregulating YAP

Abstract: Background. Acute pancreatitis (AP) is one of the most common gastrointestinal disorders, which causes death with a high mortality rate of about 30%. The study aims to identify whether the nonalcoholic fatty liver disease (NAFLD)-derived lncRNA MALAT1 participates in the inflammation of pancreatic cell and its potential mechanism. Methods. The NAFLD cell model was constructed by treating HepG2 cells with FFA. The in vitro model of acute pancreatitis (AP) was established by the administration of caerulein on AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Mechanistically, the exosome-derived lncRNA MALAT1 was upregulated significantly and inhibited the hippo-YAP pathway and autophagy in AP. The YAP1 inhibitor CA3 could increase the LC3II/LC3I expression and reduce IL-6 and TNF-α levels induced by lncRNA MALAT1, suggesting that lncRNA MALAT1 aggravated AP by suppressing autophagy via the YAP pathway ( Liu D. et al, 2022 ). However, the specific mechanism of the YAP pathway to regulate autophagy in AP is unclear.…”
Section: Lncrnas In Ap Pathogenesismentioning
confidence: 99%
“…Mechanistically, the exosome-derived lncRNA MALAT1 was upregulated significantly and inhibited the hippo-YAP pathway and autophagy in AP. The YAP1 inhibitor CA3 could increase the LC3II/LC3I expression and reduce IL-6 and TNF-α levels induced by lncRNA MALAT1, suggesting that lncRNA MALAT1 aggravated AP by suppressing autophagy via the YAP pathway ( Liu D. et al, 2022 ). However, the specific mechanism of the YAP pathway to regulate autophagy in AP is unclear.…”
Section: Lncrnas In Ap Pathogenesismentioning
confidence: 99%
“…Risk factors for AP include the presence of non-alcoholic fatty liver disease. The authors hypothesized that hepatocyte injury and the subsequent release of exosomes would foster the progression of AP [ 45 ]. Exosome-specific MALAT1 was secreted by damaged hepatocytes, which exacerbated inflammation in acinar cells by downregulating autophagy and upregulating the Hippo–YAP pathway [ 45 ].…”
Section: Exosome-specific Ncrnasmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%